Reducing Understanding of Online Gossip in the Perspective of the Qur'an: From Impact to Solution - Dita Febrianti; Wiwin Ainis Rohtih; M. Mukhid Mashuri; Miftara Ainul Mufid (JIA (Jurnal Ilmu Agama), 2025)
In this era of Society 5.0, humanity is faced with a new era marked by rapid technological advancements. With the rise of social media platforms, communication between people is no longer hindered by physical distance, making it easier and more accessible than ever before. However, recent findings suggest that the prevalence of social media today is no longer primarily about education, information, or motivation, but rather about content that goes viral, specifically “online gossip.” This study aims to discuss online gossip from the perspective of the Qur'an, analyzing its impacts and potential solutions. The method used is qualitative, employing the Tafsir Maudhu'i approach with descriptive-analytical data analysis. The results and discussion reveal that the Qur’an’s perspective on online gossip stems from feelings of insecurity and a lack of gratitude for what Allah has bestowed upon humanity. The consequences of gossip are not only spiritual and otherworldly, such as the threat of punishment in the afterlife, but also cause social harm in this world. Therefore, the highly recommended solution is to engage in regular self-reflection or introspection. By recognizing that every human being is created with their own uniqueness, strengths, and weaknesses, it is hoped that individuals can refrain from the tendency to discuss others' faults. This research contributes to reducing the phenomenon of online gossip in the midst of the rapid development of the Society 5.0 era.